Alexander the Great : From His Death to the Present Day - Boardman, John (Book collections on Project MUSE., 2019)
Alexander's defeat of the Persian Empire in 331 BC captured the popular imagination, inspiring an endless series of stories and representations that emerged shortly after his death and continues today. An art historian and archaeologist, Boardman draws on his deep knowledge of Alexander and the ancient world to reflect on the most interesting and emblematic depictions of this towering historical figure. Some of the stories in this book relate to historical events associated with Alexander's military career and some to the fantasy that has been woven around him, and Boardman relates each with his customary verve and erudition. From Alexander's biographers in ancient Greece to the illustrated Alexander "Romances" of the Middle Ages to operas, films, and even modern cartoons, this generously illustrated volume takes readers on a fascinating cultural journey as it delivers a perfect pairing of subject and author.